Islamophobia and the geopolitical strategies: An analysis of select post 9/11 novels - Abdu Latheef Kampuravan (Govt College Malappuram, University of Calicut, 2025)
This study examines the dynamic relationship between Islamophobia, post-9/11 detective fiction, and geopolitical strategies. By analyzing eight novels written by both Western and non-Western authors, it explores how Islamophobic narratives are embedded in popular literature and how they shape and reflect global political attitudes toward Muslim communities. Using theoretical frameworks such as postcolonial theory, Orientalism, Critical Race Studies, and discourse analysis, the research argues that literature functions not merely as a cultural product but as a strategic tool that reinforces ideological structures. Drawing on geopolitical theories, the study proposes a reciprocal relationship in which Islamophobic representations in fiction influence public perception and policy decisions, while geopolitical agendas further reinforce such narratives in cultural production. The analysis reveals that detective fiction often normalizes stereotypes, constructs Muslims as irrational or threatening, and legitimizes Western interventionist policies. Even works by non-Western authors tend to reproduce similar patterns, depicting Muslim societies as dysfunctional and in need of reform through Western influence. Ultimately, the study concludes that literature operates as a form of soft power that shapes political realities and sustains Orientalist binaries. It calls for critical engagement with literary texts, interdisciplinary research, and more responsible storytelling to challenge and dismantle the cycle of Islamophobic representation.
Keywords: Islamophobia; Geopolitics; Othering of Muslims; Muslim Representation; Post 9/11 literature; Orientalism